Fan motives for interacting on social media - the example of the International Table Tennis Federation and Facebook - Mathias Schubert; Jannis Seyffert (Bern Open Publishing, 2017)
Social media has become an important tool for sport organisations to interact with fans. In particular for sports that have smaller marketing budgets and that do not receive mainstream media coverage on a daily basis, social media platforms provide unique communication and marketing opportunities to overcome such challenges. This study investigates the motives of fans to communicate on the Facebook page of the International Table Tennis Federation (ITTF). It is the first study that focuses on the use of social media in the context of an international sport federation. Knowledge about the gratifications sought by fans while interacting on social media is important for organisations to develop more customised online content, as this may help to reach further goals such as maintaining public interest, reinforcing brand awareness or developing closer relationships with stakeholders. We extend the academic understanding of sport fans' motives in the context of social media and derive implications that can be relevant for managers of (niche) sport organisations with limited financial and personal resources.